Effects of different adrenaline doses on cerebral oxygenation and cerebral metabolism during cardiopulmonary resuscitation in pigs. (November 2020) - Putzer, Gabriel; Martini, Judith; Spraider, Patrick; Hornung, Rouven; Pinggera, Daniel; Abram, Julia; Altaner, Niklas; Hell, Tobias; Glodny, Bernhard; Helbok, Raimund; Mair, Peter
Abstract: Background: The influence of adrenaline during cardiopulmonary resuscitation (CPR) on the neurological outcome of cardiac arrest survivors is unclear. As little is known about the pathophysiological effects of adrenaline on cerebral oxygen delivery and cerebral metabolism we investigated its effects on parameters of cerebral oxygenation and cerebral metabolism in a pig model of CPR. Methods: Fourteen pigs were anesthetized, intubated and instrumented. After 5 min of cardiac arrest CPR was started and continued for 15 min. Animals were randomized to receive bolus injections of either 15 or 30 μg/kg adrenaline every 5 min after commencement of CPR. Results: Measurements included mean arterial pressure (MAP), intracranial pressure (ICP), cerebral perfusion pressure (CPP), cerebral regional oxygen saturation (rSO2 ), brain tissue oxygen tension (Pbt O2 ), arterial and cerebral venous blood gases and cerebral microdialysis parameters, e.g. lactate/pyruvate ratio. Adrenaline induced a significant increase in MAP and CPP in all pigs. However, increases in MAP and CPP were short-lasting and tended to decrease with repetitive bolus administration. There was no statistical difference in any parameter of cerebral oxygenation or metabolism between study groups. Conclusions: Both adrenaline doses resulted in short-lasting CPP peaks which did not translate into improved cerebral tissue oxygen tension and metabolism. Further studies are needed to determine whether other dosing regimens targeting a sustained increase in CPP, may lead to improved brain oxygenation and metabolism, thereby improving neurological outcome of cardiac arrest patients.